Physician-Modified Endovascular Gore Excluder Graft (Handmade Modified) for Complex Abdominal Aortic Aneurysm: A Step-by-Step Approach. (October 2020) - Lopez-Pena, Gabriel; Garcia-Alva, Ramon; Laparra-Escareno, Hugo; Anaya-Ayala, Javier E.; Guerrero-Hernández, Manuel; Hinojosa, Carlos A.
Endovascular repair has become the gold standard for the treatment of infrarenal abdominal aortic aneurysmal disease. Branched and fenestrated commercially custom-made devices have been developed as a treatment option for short necks or juxtarenal aneurysms. However, the lack of availability in some countries and centers, manufacturing time (6-8 weeks requirements), urgent setting in ruptured abdominal aortic aneurysms, and elevated costs make them not a widespread option. Hereby, we expose our step-by-step technique of physician modified Gore Excluder to treat complex aneurysms. Physician-modified endovascular graft (PMEG) has emerged as an alternative to open repair for the treatment of complex aortic aneurysms. The ultimate goal of fenestrations is to increase the proximal sealing zone length. The Gore C3 delivery system allows repositioning of the graft by constraining the proximal part after a back-table physician modification; the PMEG technique with the Gore Excluder C3 delivery system can be used for complex aortic aneurysms repair as an alternative treatment option.